Ant diversity in Muhan Pokhari area of Shivapuri-Nagarjun National Park, Nepal - Neupane, Prashant; Subedi, Indra Prasad (Journal of Natural History Museum, 2018)
Ant diversity was studied in Muhan Pokhari area of Shivapuri-Nagarjun National Park (SNNP)at 1,700 m to 1,900 m asl during winter and summer seasons of 2017. Ants were collected using pitfall traps, leaf litter sampling, bait and hand collection methods along a transect of50 m in each of all 5 sites (1,700 m, 1,750 m, 1,800 m, 1,850 m and 1,900 m). Altogether 817individual ants were collected representing 5 sub-families, 16 genera and 23 morpho species. Formicinae (57.67%) was the most abundant sub-family, followed by Myrmicinae (40.39%), Pseudomyrmicinae (0.8%), Ponerinae (0.73%) and Dolichoderinae (0.37%). Camponotus (437individuals) was the most abundant genus followed by Aphaenogaster (287). Species richness was higher in winter (17 morph species) than in spring (14 morph species). Shannon-Wiener diversity index (1.4618) and Evenness index (0.5539) were higher in spring season. Pitfall trap method was found most effective with highest number of individual ants (567) and of 21 species. The Shannon-Weiner diversity index was highest for pitfall method (1.3039) whereas evenness index was highest for the bait method (0.62615). Two genera Pachycondylaand Echinopla were recorded for the first time in Nepal.